BcGRP23: A novel gene involved in the chlorophyll metabolic pathway that is activated by BES1 in flowering Chinese cabbage - Zhang, Shuaiwei; Chen, Kemin; Anwar, Ali; Wang, Yudan; Yao, Shengyi; Chen, Riyuan; Song, Shiwei; Su, Wei (Frontiers in Plant Science, 2022)
Glycine-rich proteins (GRPs) are a large family of proteins that play vital roles in cell wall remodeling, metabolism and development, and abiotic stress response. Although the functions of GRPs in cell wall remodeling have been extensively characterized, only a few studies have explored their effects on chlorophyll metabolism and hormone response. Accordingly, we aimed to determine the molecular mechanism of BcGRP23 and its role in chlorophyll metabolism and the BRI1-EMS-SUPPRESSOR 1 (BES1) signaling pathway in flowering Chinese cabbage. The expression levels of BcGRP23 in the leaves and stems gradually decreased with increasing growth and development of flowering Chinese cabbage, while BcGRP23 was barely expressed after flowering. As plant growth continued, the GUS (β-glucuronidase) stain gradually became lighter in hypocotyls and was largely free of growth points. The petioles and stems of BcGRP23-silenced plants lost their green color, and the contents of chlorophyll a (Chl a) and Chl b were significantly reduced. Further research revealed that the expression levels of chlorophyll degradation-related genes were significantly increased in silenced plants compared with the control; however, the opposite was noted for the BcGRP23-overexpressing lines. The BcGRP23 promoter sequence contains numerous hormone-responsive elements. In fact, the expression of BcGRP23 was upregulated in flowering Chinese cabbage following treatment with the hormones indole-3-acetic acid (IAA), gibberellin (GA), 6-benzylaminopurine (6-BA), methyl jasmonate (MeJA), and brassinosteroid (BR). Treatment with BR led to the most significant upregulation. BES1, in response to BRs, directly activated the BcGRP23 promoter. Overall, BcGRP23 regulated the expression of chlorophyll degradation-related genes, thereby affecting the chlorophyll content. Furthermore, the expression of BcGRP23 was significantly regulated by exogenous BR application and was directly activated by BES1. These findings preliminarily suggest the molecular mechanism and regulatory pathway of BcGRP23 in the growth and development of flowering Chinese cabbage plants and their response to environmental stress.